A preliminary study on the Tangut version of the Mañjuśirī-dhaāraṇī-sūtra. (September 2018) - Guo, Yaoyao
Abstract: There is a Tangut version of the Mañjuśirī-dhāraṇī-sūtra entitled Sūtra of Counting the Merits and Virtues of Rosaries in the Mañjuśirī-dhāraṇī preserved in the Institute of Oriental Manuscripts, Russian Academy of Sciences. The paper proves by collating the nomenclatures that the Tangut text was a translation from the Chinese version of the text by Yijing rather than that of Baosiwei.